(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Anacardium occidentale L. and Mangifera indica L. has been used worldwide both for pharmaceutical, food and cosmetic industries due to the presence of biological activities of some of its metabolites. The present study comprises the correlation of antioxidant activity and antimicrobial activity in ethyl acetate extract of young leaves and bark of A. occidentale and M. indica. The activity of 1, 1-diphenyl-2-picrylhydrazyl (DPPH) on radical scavenging effect of the extracts was carried out by spectrophotometrically. All the plant extracts showed DPPH radical scavenging activity and among the extracts, A. occidentale young leaves indicated higher antioxidant potential in comparison with those of the other extracts. The antibacterial activity of various extracts was also screened against some human pathogens of clinical importance; Pseudomonas aeruginosa; Salmonella typhi; Bacillus subtilis; Escherichia coli and Staphylococcus aureus.